The Wnt antagonists DKK1 and SFRP1 are downregulated by promoter hypermethylation in systemic sclerosis - Dees, Clara; Schlottmann, Inga; Funke, Robin; Distler, Alfiya; Palumbo-Zerr, Katrin; Zerr, Pawel; Lin, Neng-Yu; Beyer, Christian; Distler, Oliver; Schett, Georg; Distler, Jörg (Annals of the Rheumatic Diseases, 2014)
Activated Wnt signalling with decreased expression of endogenous inhibitors has recently been characterised as a central pathomechanism in systemic sclerosis (SSc). Aberrant epigenetic modifications also contribute to the persistent activation of SSc fibroblasts. We investigated whether increased Wnt signalling and epigenetic changes in SSc are causally linked via promoter hypermethylation-induced silencing of Wnt antagonists.The methylation status of endogenous Wnt antagonists in leucocytes and fibroblasts was evaluated by methylation-specific PCR. 5-aza-2'-deoxycytidine was used to inhibit DNA methyltransferases (Dnmts) in cultured fibroblasts and in the mouse model of bleomycin-induced skin fibrosis. Activation of Wnt signalling was assessed by analysing Axin2 mRNA levels and by staining for ?-catenin.The promoters of DKK1 and SFRP1 were hypermethylated in fibroblasts and peripheral blood mononuclear cells of patients with SSc. Promoter hypermethylation resulted in impaired transcription and decreased expression of DKK1 and SFRP1 in SSc. Treatment of SSc fibroblasts or bleomycin-challenged mice with 5-aza prevented promoter methylation-induced silencing and increased the expression of both genes to normal levels. Reactivation of DKK1 and SFRP1 transcription by 5-aza inhibited canonical Wnt signalling in vitro and in vivo and effectively ameliorated experimental fibrosis.We demonstrate that hypermethylation of the promoters of DKK1 and SFRP1 contributes to aberrant Wnt signalling in SSc and that Dnmt inhibition effectively reduces Wnt signalling. These data provide a novel link between epigenetic alterations and increased Wnt signalling in SSc and also have translational implications because Dnmt inhibitors are already approved for clinical use.
EVALuna2:12884